Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

If f(x+1)=x^2+2, we need to rewrite the expression so as to make x+1 the basis of the expression. We can write:

x^2+2 as x^2+2x+1+1-2x=(x+1)^2+1-2x=(1+x)^2-2-2x+3=(1+x)^2-2(1+x)+3. Now replace 1+x by x: f(x)=x^2-2x+3.

Another approach is to replace x with x-1: f(x)=f(x+1-1)=(x-1)^2+2=x^2-2x+1+2=x^2-2x+3.

by Top Rated User (626k points)

Related questions

1 answer
asked Jan 3, 2015 in Pre-Algebra Answers by drmanscach Level 1 User (200 points) | 153 views
1 answer
asked May 15, 2013 in Word Problem Answers by sunflower Level 1 User (220 points) | 105 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
82,530 questions
87,085 answers
1,957 comments
3,665 users